Physico-chemical Changes During and After Ripening in Syzygium samarangense (Wax apple var. Jambu madu) Fruits: A Review - Mohammad Moneruzzaman, Khandaker; Ali, Majrashi; Amru Nasrulhaq, Boyce (2016)
Background: Background: There is increasing concern about the wax apple fruit growth and colour development as well as fruit quality, worldwide. Its great potential had been valued by the old folks and now it is getting famous as more attention given in exploring fruits and as an alternative for medicine. The aim of this review is describe in detail the physiochemical changes during color development and ripening stage. Fruit growth and color development it takes arround 5 and 2 weeks and growth pattern is sigmoidal curve. It also recommended that fruit ripening it takes only one week and fruits should not be harvested before they are ripened. Fruit juice acidity, TSS and total sugar content significantly increased during and maturing and ripening of fruits. The taste, flavor and physiochemical properties of wax apple fruit do not improve after harvest. Pre harvest treatments with growth regulators, growth promoting chemicals and phloemic stress were found to have an effect on physiochemical characteristics of wax apple at ripening and after ripening. Conclusion: The application of GA3 and NAA during fruit development stages improved the colour development and shortened the harvesting periods. Fruit quality such as firmness, fruit juice, fruit biomass, TSS and Total sugar content of fruits. C-Shaped phloemic stress stimulates colour development and increased the fruit quality. Growth promoting chemicals hydrogen peroxide also have significant role on fruit quality improvement. H2O2 application at 5 and 20 mM concentration produced better quality of fruits under field conditions. This review article provides information about wax apple fruits in detail in term of pigmentation and physicochemical characteristics of wax apple.